2013
DOI: 10.1007/s10067-013-2171-0
|View full text |Cite
|
Sign up to set email alerts
|

Aggrecanases in the human synovial fluid at different stages of osteoarthritis

Abstract: In vivo and in vitro aggrecanases degrade proteoglycan aggrecan in articular cartilage. However, the expression of aggrecanases in patients in different stages of osteoarthritis (OA) has not been investigated. This study detected the expression of a disintegrin and metalloproteinase with thrombospondin motifs 4 (ADAMTS-4) and ADAMTS-5 and their proteolytic products, ARGxx, in the synovial fluid (SF) of patients in different stages of OA. This study aimed to evaluate the expression of aggrecanases and to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 32 publications
3
43
2
Order By: Relevance
“…Western blot analysis of ADAMTS 4 and 5 in SF culture supernatants revealed the presence of the active forms of both enzymes, between 48 and 74 kDa, similar to those reported in OA synovial fluids. 30 We also observed a major band between 74 and 114 kDa, which has been described as the ADAMTS-4 proenzyme, in cartilage from OA patients, 28 as well as in SF. 9 Regarding ADAMTS-5, other authors have also reported a 70-kDa form of ADAMTS-5 in cartilage, as well as in SF from OA patients, 9,28 that could represent different degradation fragments.…”
Section: Induction Of Adamts-7 and Adamts-12 By Il-1b Or 45-kda Fn-fssupporting
confidence: 56%
“…Western blot analysis of ADAMTS 4 and 5 in SF culture supernatants revealed the presence of the active forms of both enzymes, between 48 and 74 kDa, similar to those reported in OA synovial fluids. 30 We also observed a major band between 74 and 114 kDa, which has been described as the ADAMTS-4 proenzyme, in cartilage from OA patients, 28 as well as in SF. 9 Regarding ADAMTS-5, other authors have also reported a 70-kDa form of ADAMTS-5 in cartilage, as well as in SF from OA patients, 9,28 that could represent different degradation fragments.…”
Section: Induction Of Adamts-7 and Adamts-12 By Il-1b Or 45-kda Fn-fssupporting
confidence: 56%
“…Compound 35 was then tested in a panel of metalloproteases and was found selective of aggrecanases versus matrix metalloproteases (MMPs) or TNF-a-converting enzyme (TACE) ( Table 7). This is consistent with the fact that the S 0 1 pocket, is defined in the metalloproteinase family, as the specificity pocket [26]. Indeed, in ADAMTS-5, there is a compact S 0 1 loop counting for half of the pocket [26] while in MMPs the S 0 1 pocket is mostly entirely enclosed in the S 0 1 loop.…”
Section: Activities On Related Proteasessupporting
confidence: 70%
“…This is consistent with the fact that the S 0 1 pocket, is defined in the metalloproteinase family, as the specificity pocket [26]. Indeed, in ADAMTS-5, there is a compact S 0 1 loop counting for half of the pocket [26] while in MMPs the S 0 1 pocket is mostly entirely enclosed in the S 0 1 loop. This difference result in decreased activity on MMPs for compounds displaying a longer P 0 1 group [13f].…”
Section: Activities On Related Proteasessupporting
confidence: 70%
See 2 more Smart Citations